Incidence, clinical features and survival among patients with functional pancreatic neuroendrocrine tumors - Mijušković, Ana; Camur, Viktor; Popovic, Bojana (Medicinski podmladak, 2025)
Abstract:Introduction: Neuroendocrine tumors (NET) are rare neoplasms derived from neuroendocrine cells that have the ability to synthesize biogenic amines and peptide hormones. Lungs, small and large intestine and pancreas are the most common localisation of these tumors. Depending on the existence of the hormone secretory syndrome and its clinical manifestations, NETs are divided into functional and non-functional tumors.Aim: The aim of this work was to investigate the incidence, biological behavior and survival of patients with functional pancreatic neuroendocrine tumors.Materials and methods: We analyzed 272 patients diagnosed with pancreatic NET. Tumor grade was evaluated based on pathohistological characteristics of the tissue samples obtained by biopsy or surgery, while stage was determined based on the size of the primary tumor and the presence of locoregional and/or distant dissemination. Diagnoses were established by using indicative clinical presentations and by determining baseline hormone values, appropriate functional testing and immunohistochemical confirmation of the secretory product in the tumor tissue sample.Results: Among 272 retrospectively analyzed patients, 77.6% of patients had non-functional tumors, while functional tumors were found in 22.4% cases. Functional NETs were significantly smaller and had a lower tumor grade, as well as significantly lower frequency of metastases and stage IV disease compared to the non-functional ones (p
Keywords: pancreatic neuroendocrine tumors; functional tumors; hormone syndrome; survival